Pack bonding - a low cost method to improve the wear resistance of steels / S. Darius Gnanaraj … [et al.] - Gnanaraj, S. Darius (Faculty of Mechanical Engineering (FKM) and UiTM Press, 2011)
A relatively new, low cost technique, pack bonding is presented for increasing the wear resistance of steels used in machine components. The borided and unbonded specimens were subjected to wear tests under the same conditions and using a pin-on-disc test rig and the results are compared. Other important tests like optical microscopy, microhardness tests were carried out for a comparative study. It was found that bonding significantly improves hardness and trihological behaviour of mild steel. The wear resistance of borided steel is 40% higher than mild steel and the frictional force offered by borided specimen is 70% higher than mild steel. The optical microscope shows that one layer of borite is formed which results in improved wear resistance considering the cost and quality. Pack bonding is a low cost surface hardening process, which can be profitably employed to decrease the wear in steel components in moving parts in machinery.